Genetic Mapping in Experimental Populations / [electronic resource] - Van Ooijen, J. W.; Jansen, J. (Cambridge : Cambridge University Press, 2013)
Genetic linkage maps are an increasingly important tool in both fundamental and applied research, enabling the study and deployment of genes that determine important biological traits. This concise introduction to genetic mapping in species with disomic inheritance enables life science graduate students and researchers to use mapping software to produce more reliable results. After a brief refresher on meiosis and genetic recombination, the steps in the map construction procedure are described, with explanations of the computations involved. The emphasis throughout is on the practical application of the methods described; detailed mathematical formulae are avoided and exercises are included to help readers consolidate their understanding. A chapter on recognising and solving problems provides valuable guidance for dealing with real-life situations. An extensive chapter dedicated to the more complex situation of outbreeding species offers a unique insight into the approach required for many economically important and model species, both plants and animals.
Poverty and violence are issues of global importance. In Poverty, War, and Violence in South Africa, Clifton Crais explores the relationship between colonial conquest and the making of South Africa's rural poor. Based on a wealth of archival sources, this detailed history changes our understanding of the origins of the gut-wrenching poverty that characterizes rural areas today. Crais shifts attention away from general models of economic change and focuses on the enduring implications of violence in shaping South Africa's past and present. Crais details the devastation wrought by European forces and their African auxiliaries. Their violence led to wanton bloodshed, large-scale destruction of property, and famine. Crais explores how the survivors struggled to remake their lives, including the adoption of new crops, and the world of inequality and vulnerability colonial violence bequeathed. He concludes with a discussion of contemporary challenges and the threats to democracy in South Africa.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Diploidy; Genetic Linkage; Uniparental Disomy